Composición del Consejo de Administración, control e implicaciones en la toma de decisiones estratégicas. - Vázquez Inchausti, Elena (Cuadernos de Estudios Empresariales, 2000)
Ris paper presents a model to assess the implication of board of director's composition on strategic decision making. The purpose is to analyse if a great presence of «outsiders» on the board will influence the diversification strategy of the company and, in turn, the strategies of its business units. We suppose that the relation between board of director's composition and strategy will be mediated by the choice of control systems on top management performance. Agradezco al profesor Dr. Jesús García-Tenorio Ronda y a la profesora Dra. María José Pérez Rodríguez todos los comentarios y sugerencias que han permitido mejorar este trabajo, así como la crítica de los evaluadores de esta revista. Este trabajo se enmarca en el proyecto 5EC97-1248-C0202 del Plan Nacional de l-4-D de la CICYT. 365 Elena Vázquez Jnchausti Composición del Consejo de Administración, control 1.